Relevansi Kisah Penguburan Abraham dalam Kejadian 25:7-11 bagi Perjumpaan Agama Kristen dan Islam - Abraham Gerald Pakpahan (Program Pascasarjana UKIM, 2024)
Indonesia is a pluralistic country. The Indonesian nation consists of many tribes, cultures, customs, and religions. Diversity can be a threat that gives rise to conflict on the one hand, but on the other hand, it can be an opportunity to build a life together from the diversity of potential and resources we have. Opportunities to build a life together need to be rooted in shared values of peace and solidarity. This research aims to provide one of the foundations for the values of peace, dialogue, and solidarity between religious communities, especially between Christianity and Islam, by rooting it in the meaning of the Biblical narrative regarding Abraham's burial in Genesis 25:7-11. With a hermeneutic approach, the author focuses on the events of Abraham's burial, especially the presence of Isaac and Ishmael to bury their father. The story of the meeting of Isaac and Ishmael, two figures who were later seen as representatives of Christianity and Islam, became the basis for weaving meaning and relevance for encounters and dialogue between two different religious communities.